Negative photosensitive resin composition for spacer

By using the negative photosensitive resin composition for spacers, the display defects, voltage retention rate drop and thickness deviation caused by the existing spacer materials in the liquid crystal panel manufacturing process are solved, and higher liquid crystal dripping efficiency, better friction resistance and voltage retention rate are achieved.

CN119556524APending Publication Date: 2025-03-04SHANGHAI WINSCENE TECH CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411754345.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-02
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

There are many problems in the manufacturing process of the existing spacer material, including affecting the mapping or obstruction of the liquid crystal movement, reducing the contrast of the liquid crystal panel, resulting in display defects, and problems of a decrease in voltage retention rate and thickness deviation.

Method used

A negative photosensitive resin composition for spacers is used, which includes an alkali-soluble acrylate resin composed of chemical formula 1 and chemical formula 2, a crosslinked acrylic monomer, a photopolymerization initiator, a silicon-based compound and a solvent. The composition forms spacers on the substrate by spin coating or slit spin coating.

Benefits of technology

The negative photosensitive resin composition for spacer can reduce defects in unfilled areas caused by the dropping amount of liquid crystal, prevent damage caused by pressure on the color filter, overcome process thickness deviations, and do not dissolve ions or impurities, maintain voltage retention, and improve liquid crystal alignment and friction resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005165862440000031
    Figure BDA0005165862440000031
  • Figure BDA0005165862440000032
    Figure BDA0005165862440000032
  • Figure BDA0005165862440000061
    Figure BDA0005165862440000061
Patent Text Reader

Abstract

The negative photosensitive resin composition for a spacer includes an alkali-soluble acrylate resin in which polymers each composed of Chemical Formula 1 and Chemical Formula 2 are mixed with each other, a crosslinked acrylic monomer having at least two acrylic double bonds, a photopolymerization initiator, a silicon-based compound including an epoxy group or an amine group, and a solvent, the chemical formula 1 is synthesized by polymerizing 4, 4 '-(9H-fluorene-9-subunit) bisphenol, chloropropane methyl, acrylic acid and 4, 4'-diphthalic anhydride, and the chemical formula 2 is synthesized by polymerizing 1, 1, 2, 2-4 (p-hydroxyphenyl) ethane, chloropropane methyl, acrylic acid and 4, 4 '-diphthalic anhydride.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] Embodiments of the present invention relate to a negative photosensitive resin composition for a spacer, and more particularly, to a negative photosensitive resin composition for a spacer that can improve not only developability but also elastic recovery rate and adhesion to a substrate. Background Art

[0002] The liquid crystal panel and the touch panel include a color filter (CF) substrate, a thin film transistor (TFT) substrate, and a spacer for maintaining a constant interval between the substrates.

[0003] In the past, the spacers were made of spacer particles, mainly glass beads or plastic beads of a specific particle size, etc. It is known that since the spacer particles are randomly scattered on the substrate, when the spacers are present in the effective pixel portion, the spacers reflect or hinder the movement of the liquid crystal, thereby reducing the contrast of the liquid crystal panel.

[0004] Therefore, a photolithography process is used to form a photosensitive spacer in an area other than the effective pixel portion. According to the photolithography process, the cell gap can be freely adjusted by slot die coating, which not only solves the inconvenience of the LCD panel using beads as spacers in the past, that is, it is necessary to purchase new beads of different particle sizes to adjust the cell gap, but also has the advantage that the shape and size of the pattern for determining the physical feature can be freely adjusted by a predetermined mask.

[0005] On the other hand, in the process of manufacturing a liquid crystal panel or a touch panel, a spacer composed of a photosensitive resin is formed on a substrate, and then an alignment film composed of liquid crystal is formed. In order to form the alignment film, an alignment agent coating film is generally formed by coating and drying an alignment agent, and then a rubbing process of rubbing the alignment agent coating film is performed.

[0006] Display defects may occur when the spacer or alignment film is peeled off from the substrate during the rubbing process. Alternatively, during the rubbing process, residues caused by the photosensitive resin composition for forming the spacer are present in the alignment film, and abnormalities may occur in the liquid crystal alignment.

[0007] Furthermore, since the spacer included in the liquid crystal panel or the touch panel is in direct contact with the liquid crystal, when ionic substances or impurities are dissolved from the spacer, the voltage holding ratio of the liquid crystal may be reduced.

[0008] As described above, the spacer formed of the photosensitive resin should not affect the voltage holding ratio, have high friction resistance, not affect the liquid crystal alignment, and also need to have developability, high sensitivity, thermal stability and size stability.

[0009] For the existing resin composition used to form the spacer, attempts are made to improve the curing characteristics and curing degree using acrylic resin to improve characteristics such as pattern shape, resolution, voltage holding rate, friction resistance, developability, high sensitivity, thermal stability, dimensional stability, and the amount of deformation and restoring force that affect when bonding TFT panels and CF panels.

[0010] However, since the spacer having the acrylic resin has high compressive strength and high restoring force to restore the original cell gap after deformation by external force, it has rigid physical properties. Therefore, the rigid spacer cannot absorb external force, which may cause damage or destruction to the TFT substrate or CF substrate.

[0011] On the other hand, when the filling process of vacuum-injecting liquid crystal is performed after the conventional bonding process of bonding the TFT substrate and the CF substrate, the filling process takes too long. In order to shorten the filling process time, a new process of performing a bonding process of bonding the TFT board and the CF board after performing a dripping process of dripping liquid crystal at one time has been developed, but the conventional spacer lacks a margin for the liquid crystal dripping process due to insufficient deformation, resulting in a problem of filling defects. Summary of the invention

[0012] Technical issues

[0013] Embodiments of the present invention provide a negative photosensitive resin composition for a spacer, which can reduce defects in unfilled areas caused by liquid crystal dripping, prevent damage caused by pressure applied from a color filter (CF) substrate, and overcome thickness deviations occurring during the process.

[0014] The embodiment of the present invention provides a negative photosensitive resin composition for a spacer, which can suppress the decrease of voltage holding ratio by not dissolving ions and impurities into liquid crystals, thereby suppressing the adverse effects during the liquid crystal alignment period.

[0015] Technical Solution

[0016] The negative photosensitive resin composition for a spacer according to an embodiment of the present invention includes: an alkali-soluble acrylate resin in which polymers composed of the following chemical formula 1 and chemical formula 2 are mixed with each other; a cross-linked acrylic monomer having at least two acrylic double bonds; a photopolymerization initiator; a silicon-based compound including an epoxy group or an amine group; and a solvent.

[0017] The chemical formula 1 is synthesized by polymerization of 4,4'-(9H-fluorene-9-ylidene)bisphenol: chloropropylmethyl: acrylic acid: 4,4'-biphthalic anhydride.

[0018] The chemical formula 2 is synthesized by polymerization of 1,1,2,2-4 (p-hydroxyphenyl) ethane: methyl chloropropane: acrylic acid: 4,4'-diphthalic anhydride.

[0019] [Chemical formula 1]

[0020]

[0021] [Chemical formula 2]

[0022]

[0023] In the Chemical Formula 1 and the Chemical Formula 2, n is a natural number ranging from 1 to 10. In the Chemical Formula 2, R1 and R2 are each independently an epoxy group.

[0024] In one embodiment of the present invention, it may include: a) 5 to 50 wt% of the alkali-soluble acrylate resin; b) 5 to 30 wt% of the cross-linked acrylic monomer; c) 0.01 to 5 wt% of the photopolymerization initiator; d) 0.0001 to 5 wt% of the silicon-based compound; and e) the remainder of the solvent.

[0025] Wherein, the solid content of the negative photosensitive resin composition may be 10 to 50% by weight.

[0026] In one embodiment of the present invention, the resin having the Chemical Formula 1 may have a weight average molecular weight ranging from 5,000 to 20,000.

[0027] In one embodiment of the present invention, the resins of Chemical Formula 1 and Chemical Formula 2 may have a weight ratio of 1:3 to 50.

[0028] In one embodiment of the present invention, the cross-linked acrylic monomer may be one or more selected from the group consisting of 1,4-butanediol diacrylate, 1,3-butanediol diacrylate, ethylene glycol diacrylate, pentaerythritol tetraacrylate, triethylene glycol diacrylate, polyethylene glycol diacrylate, dipentaerythritol diacrylate, sorbitol triacrylate, bisphenol A diacrylate derivatives, trimethylolpropane triacrylate, dipentaerythritol polyacrylate and their methacrylates.

[0029] In one embodiment of the present invention, the photopolymerization initiator may include a triazine compound, a benzoin compound, an acetophenone compound, an xanthone compound or an imidazole compound, wherein the triazine compound includes 2,4-bistrichloromethyl-6-p-methoxyphenylvinyl-s-triazine, 2-p-methoxyphenylvinyl-4,6-bistrichloromethyl-s-triazine, 2,4-trichloromethyl-6-triazine or 2,4-trichloromethyl-4-methylnaphthyl-6-triazine; the benzoin compound includes benzophenone or p-(ethylamino)benzophenone; the acetophenone compound includes 2,2-dichloro-4-phenyl Oxyacetophenone, 2,2-diethoxyacetophenone, 2,2-dibutoxyacetophenone, 2-hydroxy-2-methylpropiophenone or p-tert-butyltrichloroacetophenone; the xanthone compounds include xanthone, thioxanthone, 2-methylthioxanthone, 2-isobutylthioxanthone, 2-dodecylthioxanthone, 2,4-dimethylthioxanthone or 2,4-diethylthioxanthone; the imidazole compounds include 2,2-bis-chlorophenyl-4,5,4,5-tetraphenyl-2-1,2-biimidazole or 2,2-bis(2,4,6-tricyanophenyl)-4,4,5,5-tetraphenyl-1,2-biimidazole.

[0030] In one embodiment of the present invention, the silicon-based compound can be one or more selected from the group consisting of (3-glycidyloxypropyl)trimethoxysilane, (3-glycidyloxypropyl)triethoxysilane, (3-glycidyloxypropyl)methyldimethoxysilane, (3-glycidyloxypropyl)trimethoxysilane, (3-glycidyloxypropyl)dimethylethoxysilane, 3,4-epoxybutyltrimethoxysilane, 3,4-epoxybutyltriethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltriethoxysilane and aminopropyltrimethoxysilane.

[0031] Technical Effects

[0032] The negative photosensitive resin composition for spacers according to the embodiments of the present invention can reduce the defects of the unfilled area caused by the amount of liquid crystal dripping, can prevent the damage caused by the pressure on the color filter (CF), and can overcome the thickness deviation caused by the process. In addition, the negative photosensitive resin composition for spacers according to the embodiments of the present invention does not dissolve ions and impurities into the liquid crystal, thereby having the effect of not reducing the voltage holding rate and not affecting the liquid crystal alignment.

[0033] Furthermore, the negative photosensitive resin composition for spacers according to the embodiments of the present invention has excellent friction resistance, sufficient voltage holding ratio and liquid crystal alignment, and has excellent developability, thermal stability, size stability, compressive strength and softness of the spacer. DETAILED DESCRIPTION

[0034] The embodiments of the present invention are described in detail below. However, the present invention is not necessarily constituted as defined in the following embodiments, but can be embodied in various forms different from this. The following embodiments are provided to ensure that the present invention can be completed completely. In addition, the present invention is provided to fully convey the scope of the present invention to those of ordinary skill in the art to which the present invention belongs.

[0035] When an element is described as being configured or connected to another element in an embodiment of the present invention, the element may be directly configured or connected to the other element, and other elements may be provided between them. Alternatively, when an element is described as being directly configured or connected to another element, other elements may not exist between them. The terms first, second, third, etc. may be used to describe various items such as various elements, components, regions, layers, and / or parts, but the items are not limited by these terms.

[0036] The technical terms used in the embodiments of the present invention are only used to illustrate specific embodiments and are not used to limit the present invention. In addition, unless otherwise specified, all terms, including technical and scientific terms, have the same meaning as those understood by ordinary technicians in the technical field of the present invention. Regarding the above terms such as terms defined in general dictionaries, they will be interpreted as having the same meaning as their meaning in the description of the relevant technology and the present invention, and will not be intuitively interpreted as ideal or excessive appearance unless clearly defined.

[0037] The photosensitive resin composition for a spacer according to an embodiment of the present invention includes: an alkali-soluble acrylate resin in which polymers composed of the following chemical formulas 1 and 2 are mixed with each other, a cross-linked acrylic monomer having at least two acrylic double bonds, a photopolymerization initiator, a silicon-based compound including an epoxy group or an amine group, and a solvent.

[0038] [Chemical formula 1]

[0039]

[0040] [Chemical formula 2]

[0041]

[0042] In the Chemical Formula 1 and Chemical Formula 2, n is a natural number ranging from 1 to 10.

[0043] In the Chemical Formula 2, R1 and R2 are each independently an epoxy group.

[0044] Regarding the alkali-soluble acrylate resin used in the present invention, it is preferred that the alkali-soluble acrylate resins are used in combination.

[0045] The alkali soluble acrylate resin has a weight average molecular weight ranging from 5000 to 20000, more preferably from 8000 to 15000. When the weight average molecular weight of the alkali soluble acrylate resin is within the range, the developing time is reduced and the residual film removal rate can be improved.

[0046] As the cross-linked acrylic monomer including at least two double bonds, 1,4-butanediol diacrylate, 1,3-butylene glycoldiacrylate, ethylene glycol diacrylate, pentaerythritol tetraacrylate, triethylene glycol diacrylate, polyethylene glycol diacrylate, dipentaerythritol diacrylate, sorbitol triacrylate, bisphenol A diacrylate derivatives, trimethylol propanetriacrylate, dipentaerythritol polyacrylate or methacrylates thereof may be used.

[0047] Preferably, the cross-linked acrylic monomer including at least two double bonds is present in an amount of 5 to 30% by weight in the photosensitive resin composition. When the content is less than 5% by weight, the photosensitive resin composition for a spacer may not be flexible, and when the content exceeds 30% by weight, the developability and adhesion may be reduced.

[0048] As the photopolymerization initiator, triazine compounds, benzoin compounds, In some embodiments, the present invention relates to a benzophenone compound, an acetophenone compound, a xanthone compound or an imidazole compound. Specifically, triazine compounds such as 2,4-bistrichloromethyl-6-p-methoxystyryl-s-triazine, 2-p-methoxystyryl-4,6-bistrichloromethyl-s-triazine, 2,4-trichloromethyl-6-triazine and 2,4-trichloromethyl-4-methylnaphthyl-6-triazine can be used; benzophenone, p-(diethylamino)benzophenone and p-(diethylamino)benzophenone can be used. benzoin compounds such as 2,2-dichloro-4-phenoxyacetophenone, 2,2-diethoxyacetophenone, 2,2-dibutoxyacetophenone, 2-hydroxy-2-methylpropiophenone, pt-butyltrichloroacetophenone, etc.; acetophenone compounds such as xanthone, thioxanthone, 2-methylthioxanthone, etc. Thioxanthone, 2-isobutylthioxanthone, 2-dodecylthioxanthone, 2,4-dimethylthioxanthone, 2,4-diethylthioxanthone, and other xanthone compounds;Or imidazole compounds such as 2,2-bis-2-chlorophenyl-4,5,4,5-tetraphenyl-2-1,2-bisimidazole, 2,2-bis(2,4,6-tricyanophenyl)-4,4,5,5-tetraphenyl-1,2-bisimidazole, etc.;

[0049] Preferably, the content of the photopolymerization initiator in the photosensitive resin composition is 0.1 to 5% by weight, and more preferably 1 to 2% by weight. When the content is less than 0.1% by weight, the curing degree decreases, and it is difficult to achieve a normal spacer shape due to low sensitivity, and the straightness of the pattern is also poor. When the content exceeds 5% by weight, storage stability problems may occur, and the resolution may decrease due to high curing degree, and there is a problem that residual film is likely to occur outside the formed pattern.

[0050] As the silicon-based compound including an epoxy group or an amine group, (3-glycidoxypropyl)trimethoxysilane, (3-glycidoxypropyl)triethoxysilane, (3-glycidoxypropyl)methyldimethoxysilane, (3-glycidoxypropyl)trimethoxysilane, (3-glycidoxypropyl)trimethoxysilane, (3-glycidoxypropyl)triethoxysilane, (3-glycidoxypropyl)methyldimethoxysilane, (3-glycidoxypropyl)trimethoxysilane, (3-glycidoxypropyl)dimethylethoxysilane, The invention also includes one or more of the group consisting of 3,4-epoxybutyltrimethoxysilane, 3,4-epoxybutyltrimethoxysilane, 3,4-epoxybutyltriethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltriethoxysilane and aminopropyltrimethoxysilane.

[0051] Preferably, the content of the silicon-based compound including an epoxy group or an amine group in the photosensitive resin composition is 0.0001 to 5% by weight, and more preferably 0.1 to 1% by weight. When the content is less than 0.0001% by weight, the adhesion is reduced, and there is a problem that the spacer falls off due to the reduced adhesion. When the content exceeds 5% by weight, there may be a problem of storage stability, and there is a problem that the spacer falls off due to excessive use.

[0052] The solvent is selected based on solubility, coating properties, etc. Specifically, propylene glycol monoethyl ether acetate, ethoxypropionateethyl, butyl acetate, 3-methoxypropionate methyl ester, ethylene glycol monomethyl ether acetate, propylene glycol monomethyl ether, propylene glycol methylether acetate, diethylene glycol dimethyl ether, diethylene glycol methylethyl ether, cyclohexanone, ethyl 3-methoxypropionate or methyl 3-ethoxypropionate can be used. In particular, propylene glycol monoethyl ether acetate, 3-methoxypropionate methyl ester or diethylene glycol methylethyl ether is preferably used.

[0053] The content of the solvent can be changed according to the viscosity or the total solid content in the composition. The solvent is included in the remaining amount other than the solid components used in the spacer composition of the present invention. In particular, it is preferred to use propylene glycol monoethyl ether acetate in an amount of 50 to 100 weight % in the total amount of the solvent. When the content of the solvent is within the above range, the thickness deviation cannot be overcome, and therefore there is a problem of reduced uniformity of the spacer photosensitive resin composition.

[0054] In addition, the photosensitive resin composition for spacers of the present invention may further contain additives such as surfactants, curing accelerators, pigments, etc. as needed. In particular, silicone-based or acrylic surfactants can be used as the surfactant.

[0055] Preferably, the content of the additive in the photosensitive resin composition is less than or equal to 2 wt %. When the content exceeds 2 wt %, residual film may be generated or stability may be reduced, and ions and impurities may be dissolved into the liquid crystal.

[0056] In addition, the present invention provides a spacer forming method, a spacer obtained by the method, and a liquid crystal display element using the spacer. The spacer forming method is characterized by using a negative photosensitive resin composition for a spacer containing the above-mentioned components. The spacer forming method is as follows.

[0057] First, the spacer photosensitive resin composition of the present invention is applied to the substrate surface by spin coating, slit spin (FAS, slit & spin) coating, slit coating, etc., and after removing the solvent in a vacuum process, the residual solvent is removed by pre-baking to form a coating film. At this time, the pre-baking is preferably performed at a temperature of 70 to 110° C. for 1 to 5 minutes.

[0058] Then, the formed coating film is irradiated with light having a composite wavelength of g, h, and I lines according to a pattern prepared in advance, and is developed with a developer to remove unnecessary portions to form a predetermined pattern.

[0059] The developer is preferably an alkaline aqueous solution, and specifically can be an inorganic base such as tetramethylammonium hydroxide, sodium hydroxide, potassium hydroxide, sodium carbonate, etc.; a primary amine such as ethylamine, n-propylamine, etc.; a secondary amine such as diethylamine, n-propylamine, etc.; a tertiary amine such as trimethylamine, methyl diethylamine, dimethyl ethylamine, triethylamine, etc.; an alcohol amine such as dimethylethanolamine, methyl diethanolamine, triethanolamine, etc.; or an aqueous solution of a quaternary ammonium salt such as tetramethylammonium hydroxide, tetraethylammonium hydroxide, etc.

[0060] Here, the developer is used by dissolving the alkaline compound at a concentration of 0.01 to 10% by weight, and a suitable amount of a surfactant may be added.

[0061] Alternatively, after development with the developer described above, the unnecessary portion may be removed by washing with ultrapure water for 30 to 90 seconds and dried to form a pattern, and then heated at 80 to 250° C. for 30 to 120 minutes in an oven or other heating device to obtain a final pattern.

[0062] The negative photosensitive resin composition for spacers according to the present invention can reduce the defects of unfilled areas caused by the amount of liquid crystal dripping, can prevent damage caused by pressure on the color filter (CF), can overcome the thickness deviation caused by the process, and because ions and impurities are not dissolved into the liquid crystal, the voltage holding rate is not reduced and the liquid crystal alignment is not affected. In addition, the photosensitive resin composition for spacers of the present invention has excellent friction resistance, sufficient voltage holding rate and liquid crystal alignment, and has excellent developability, high sensitivity, thermal stability, size stability and compression strength.

[0063] In order to help understand the present invention, preferred embodiments are given below. However, the following embodiments are only for illustrating the present invention, and the scope of the present invention is not limited to the following embodiments.

[0064] Synthesis example

[0065] [Synthesis example 1]

[0066] 4,4'-(9H-fluorene-9-ylidene)bisphenol [Sigma-Aldrich]: methyl chloropropane: acrylic acid: 4,4'-diphthalic anhydride were added to a 1L jacketed reactor equipped with a cooling tube and a stirrer at a weight ratio of 30:10:30:30, 1% of the total weight of V-65 was added as a polymerization initiator, and 1% of the total weight of tert-butylhydroquinone was added as a polymerization inhibitor. In addition, propylene glycol methyl ether acetate was added as a solvent, using 60% of the total weight of the solvent, and stirring was started after nitrogen substitution. The stirring speed was preferably 80 rpm. In addition, the reaction solution was heated to 60°C and maintained at this temperature for 6 hours to obtain a polymer resin of chemical formula 1 as an alkali-soluble acrylate resin.

[0067] [Synthesis example 2]

[0068] 1,1,2,2-4 (p-hydroxyphenyl) ethane (1,1,2,2-tetrakis (P-hydroxyphenyl) ethane) [Sigma-Aldrich]: methyl chloropropane: acrylic acid: 4,4'-diphthalic anhydride were added in a 1L jacketed reactor equipped with a cooling tube and a stirrer at a weight ratio of 30:10:30:30, and 1% of the total weight of V-65 was added as a polymerization initiator, and 1% of the total weight of tert-butylhydroquinone was added as a polymerization inhibitor. In addition, propylene glycol methyl ether acetate was added as a solvent, using 60% of the total weight of the solvent, and stirring was started after nitrogen substitution. The stirring speed was preferably 80 rpm. In addition, the reaction solution was heated to 60°C and maintained at this temperature for 6 hours to obtain a polymer resin of chemical formula 2 as an alkali-soluble acrylic resin.

[0069] [Example]

[0070] Example 1

[0071] A liquid photosensitive resin composition for a spacer was prepared by using a polymer having chemical formula 1 of Synthesis Example 1 and a polymer having chemical formula 2 of Synthesis Example 2 mixed in a ratio of 1:3 as an alkali-soluble acrylic resin, using dipentaerythritol polyacrylate as a cross-linked acrylic monomer having at least two acrylic double bonds and mixing 10 wt %, using 2-(3,4-epoxycyclohexyl)ethyltriethoxysilane and 0.1 wt % of aminopropyltrimethoxysilane as a silicon-based compound including an epoxy group or an amine group, using 1 wt % of Irgacure 907 (manufactured by Ciba Specialty Chemicals) and 2.0 wt % of 4,4-bisdiethylaminobenzophenone as an initiator, and using 46.8 wt % of propylene glycol methyl ether acetate as a solvent.

[0072] In the case of Examples 1 and 2 and Comparative Examples 1 to 4, a liquid photosensitive resin composition for a spacer was prepared in the same manner as in Example 1 except that the components and composition ratios shown in Table 1 were used. Here, the units in Table 1 are weight %. In Chemical Formula 2, R1 and R2 are epoxy groups, each having a molecular weight of 10,000, and dipentaerythritol polyacrylate is used as a cross-linking acrylic monomer.

[0073] [Table 1]

[0074]

[0075] Using the photosensitive resin compositions for spacers prepared in Examples 1 to 2 and Comparative Examples 1 to 4, development characteristics, deformation amount and restoring force of spacers, and compression failure characteristics of spacers were evaluated as follows.

[0076] 1. Development characteristics

[0077] The photosensitive resin compositions for spacers prepared in Examples 1 to 2 and Comparative Examples 1 to 4 were spin-coated on the retention surface so as to have a film thickness of 4 μm, and then dried on a hot plate at 90° C. for 2 minutes to obtain a coating film.

[0078] After placing a photomask on the obtained coating film, an ultra-high pressure mercury lamp emitting light at a wavelength of 200 to 400 nm was used with a wavelength of 365 nm as the reference and a light intensity of about 40 mJ / cm 2 The micropattern was exposed for a certain time and developed with a KOH developer (DCD-260CF, manufactured by Dongjin Semichem) through a spray nozzle for a certain time. The developability was evaluated based on the adhesion and pattern shape of the developed micropattern. The results are shown in Table 2 below.

[0079] [Table 2]

[0080]

[0081] As shown in Table 2 above, the photosensitive resin compositions of Examples 1 to 2 according to the present invention have good pattern shapes and adhesion at mask sizes of 30, 20, and 10 μm, which are significantly superior to Comparative Examples 1 to 3.

[0082] When measuring the development characteristics, the developed micro pattern was hard-baked in a drying oven at 230° C. for 20 minutes to obtain a measurement sample.

[0083] The measured spacer in the measured sample was measured based on the mask pattern of 20μm. A dynamic ultra micro hardness tester (DUH, Shimadzu) was used to press the spacer with a force of 5gf using a 50μm circular flat indenter to measure the inflection point of the spacer caused by external force and observe the deformation and restoring force during compression. The results are shown in Table 3.

[0084] [Table 3]

[0085]

[0086] As shown in Table 3 above, it can be confirmed that the deformation and recovery of the spacers formed by the photosensitive resin compositions of Examples 1 to 2 prepared according to the present invention are significantly improved compared to the spacers of Comparative Examples 1 to 4, and the softness generated by the improved deformation reduces the thickness deviation of the spacers in the process to make the thickness uniform, showing excellent uniformity. This is different from the existing hard spacers, which have uneven cell gaps or are over-pressed due to the thickness deviation in the process of bonding the color filter (CF) plate and the TFT plate, resulting in the color filter (CF) plate and the TFT being broken.

[0087] In addition, when an error in the amount of liquid crystal dripped results in insufficient liquid crystal being filled into the cell gap, the flexibility can reduce defects in the unfilled area by allowing further deformation.

[0088] Therefore, it is expected that the spacer formed according to the present invention is excellent in compressive strength and restoring force to return to the original cell gap after being deformed by external force.

[0089] 2. Compression failure characteristics of spacers

[0090] The measurement was performed using a measurement sample obtained when measuring the deformation and restoring force characteristics of the spacer, wherein the measured spacer was based on a mask pattern of 20um, and a dynamic ultra microhardness tester (DUH: dynamic ultra microhardness tester, shimadzu) was used to press the spacer with a force of 100gf using a 50μm circular flat indenter to measure the force (force) and deformation of the inflection point occurring when the spacer was destroyed, and the deformation and restoring force during compression were observed. The results are shown in Table 4.

[0091] [Table 4]

[0092]

[0093] It can be confirmed from Table 4 that, compared with the spacers of Comparative Examples 1 to 4, the spacers formed using the photosensitive resin compositions of Examples 1 to 2 prepared according to the present invention are still significantly superior in deformation amount and inflection point when compressed at 100 gf.

[0094] 3. Friction resistance of spacers

[0095] The micro pattern developed in the same manner as the above-mentioned development characteristic method was hard-baked in a drying oven at 230°C for 20 minutes to obtain a measurement sample. The measurement spacer in the measurement sample was measured based on the mask pattern of 10, 20, and 30 μm. The adhesion of the spacer after rubbing and the presence of scratches on the surface were observed on the rubber end using a homemade rubbing tester (rubbing test) that can adjust the rotation speed, rubbing depth, and table movement speed. The results are shown in Tables 5 and 6 below.

[0096] [Table 5]

[0097]

[0098] [Table 6]

[0099]

[0100] It can be confirmed from Table 5 and Table 6 that the spacers formed using the photosensitive resin compositions of Examples 1 to 2 prepared according to the present invention have excellent adhesion and friction resistance compared with the spacers of Comparative Examples 1 to 4.

[0101] 4. Voltage retention characteristics of spacers

[0102] The spacer obtained by hard-baking the micro pattern developed in the same way as the development characteristic method in a drying oven at 230° C. for 20 minutes was used to bond the upper and lower plates with ITO patterns and inject liquid crystal to make the liquid crystal unit to be tested, and the voltage holding ratio was obtained using VHRM 105 (AUTRONIC COMPANY). The results are shown in Table 7 below.

[0103] [Table 7]

[0104]

[0105] It can be confirmed from the above table that the spacers of Examples 1 and 2 do not cause a decrease in voltage holding ratio due to ion elution or impurities.

[0106] 5. Uniformity of spacer thickness

[0107] The thickness uniformity of the spacer within the substrate was obtained by measuring the thickness of the micropattern developed in the same manner as the development method and hard-baking it in a drying oven at 230° C. for 20 minutes using a profiler (Profiler P-15, TENCO). The results are shown in Table 8 below.

[0108] [Table 8]

[0109]

[0110] It can be confirmed from the above table that, compared with the comparative example, Examples 1 and 2 cannot show excellent thickness uniformity, and when the spacer has a structure in which Examples 1 and 2 are mixed at a certain ratio, excellent thickness uniformity can be obtained.

[0111] [Effects of the invention]

[0112] The negative photosensitive resin composition according to the present invention has excellent properties such as adhesion, heat resistance, insulation, flatness, and chemical resistance, and is therefore suitable as an image forming material for a liquid crystal display element, and in particular has excellent sensitivity, residual film rate, and UV transmittance when forming an organic insulating film of a liquid crystal display element, and is therefore suitable for use as an interlayer organic insulating film, and can be used as a resist resin for an overcoat, a resist resin for a black matrix, a resist resin for a column spacer, or a resist resin for a color filter to improve sensitivity and residual film rate.

[0113] Although only specific examples of the present invention have been described in detail above, it is obvious to a person skilled in the art that various changes and modifications can be made within the technical scope of the present invention. Of course, these changes and modifications are within the scope of the appended claims.

Claims

1. A negative photosensitive resin composition for spacers, characterized in that: include: a) an alkali-soluble acrylate resin in which polymers of the following chemical formula 1 and chemical formula 2 are mixed with each other; b) a crosslinking acrylic monomer having at least two acrylic double bonds; c) a photopolymerization initiator; d) a silicon-based compound including an epoxy group or an amine group; and e) Solvent The chemical formula 1 is synthesized by polymerization of 4,4'-(9H-fluorene-9-ylidene)bisphenol: methyl chloropropane: acrylic acid: 4,4'-diphthalic anhydride. The chemical formula 2 is synthesized by polymerization of 1,1,2,2-4 (p-hydroxyphenyl) ethane: methyl chloropropane: acrylic acid: 4,4'-diphthalic anhydride. [Chemical formula 1] [Chemical formula 2] In the chemical formula 1 and the chemical formula 2, n is a natural number ranging from 1 to 10, In the Chemical Formula 2, R1 and R2 are each independently an epoxy group.

2. The negative photosensitive resin composition for spacers according to claim 1, characterized in that: include: a) 5 to 50 wt % of the alkali-soluble acrylate resin; b) 5 to 30 wt% of the cross-linked acrylic acid monomer; c) 0.01 to 5 wt % of the photopolymerization initiator; d) 0.0001 to 5 wt% of the silicon-based compound; and e) The remainder of the solvent.

3. The negative photosensitive resin composition for spacers according to claim 2, characterized in that: The negative photosensitive resin composition has a solid content of 10 to 50% by weight.

4. The negative photosensitive resin composition for spacers according to claim 1, characterized in that: The resin having the Chemical Formula 1 has a weight average molecular weight ranging from 5,000 to 20,000.

5. The negative photosensitive resin composition for spacers according to claim 1, characterized in that: The resins of Chemical Formula 1 and Chemical Formula 2 have a weight ratio of 1:3 to 50.

6. The negative photosensitive resin composition for spacers according to claim 1, characterized in that: The cross-linked acrylic monomer is one or more selected from the group consisting of 1,4-butanediol diacrylate, 1,3-butanediol diacrylate, ethylene glycol diacrylate, pentaerythritol tetraacrylate, triethylene glycol diacrylate, polyethylene glycol diacrylate, dipentaerythritol diacrylate, sorbitol triacrylate, bisphenol A diacrylate derivatives, trimethylolpropane triacrylate, dipentaerythritol polyacrylate and their methacrylates.

7. The negative photosensitive resin composition for spacers according to claim 1, characterized in that: The photopolymerization initiator includes triazine compounds, benzoin compounds, acetophenone compounds, xanthone compounds or imidazole compounds. The triazine compounds include 2,4-bistrichloromethyl-6-p-methoxyphenylvinyl-s-triazine, 2-p-methoxyphenylvinyl-4,6-bistrichloromethyl-s-triazine, 2,4-trichloromethyl-6-triazine or 2,4-trichloromethyl-4-methylnaphthyl-6-triazine; The benzoin compounds include benzophenone or p-(ethylamino)benzophenone; The acetophenone compounds include 2,2-dichloro-4-phenoxyacetophenone, 2,2-diethoxyacetophenone, 2,2-dibutoxyacetophenone, 2-hydroxy-2-methylpropiophenone or p-tert-butyltrichloroacetophenone; The xanthone compounds include xanthone, thioxanthone, 2-methylthioxanthone, 2-isobutylthioxanthone, 2-dodecylthioxanthone, 2,4-dimethylthioxanthone or 2,4-diethylthioxanthone; The imidazole compounds include 2,2-bis-chlorophenyl-4,5,4,5-tetraphenyl-2-1,2-biimidazole or 2,2-bis(2,4,6-tricyanophenyl)-4,4,5,5-tetraphenyl-1,2-biimidazole.

8. The negative photosensitive resin composition for spacers according to claim 1, characterized in that: The silicon-based compound is one or more selected from the group consisting of (3-glycidyloxypropyl)trimethoxysilane, (3-glycidyloxypropyl)triethoxysilane, (3-glycidyloxypropyl)methyldimethoxysilane, (3-glycidyloxypropyl)trimethoxysilane, (3-glycidyloxypropyl)dimethylethoxysilane, 3,4-epoxybutyltrimethoxysilane, 3,4-epoxybutyltriethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltriethoxysilane and aminopropyltrimethoxysilane.

Citation Information

Cited By

  • Negative photosensitive insulating film composition and insulating film using same

    CN122172508A